Parents' experiences managing their child's complicated postoperative recovery. (March 2018) - Purcell, Mary; Longard, Julie; Chorney, Jill; Hong, Paul
Abstract: Objective: Tonsillectomy is commonly performed as same-day surgery and parents are heavily relied upon for management of children's postoperative recovery. The objective of this study was to provide an in-depth description of the experiences parents face when managing their child's complicated postoperative recoveries at home. Methods: An exploratory qualitative study at an academic pediatric hospital in Eastern Canada was performed. Participants included 12 parents of children aged 3–6 years who underwent adeno/tonsillectomy and experienced unexpected outcomes or complications during the postoperative recovery period. Parents participated in semi-structured interviews within 6 months of their child's surgery. Interviews were transcribed verbatim and thematic analysis was used to identify themes in the parents' experiences. Results: Parents described struggling to make the decision to come back to hospital, that adequate information does not prevent emotional difficulties, and feeling somewhat responsible for the unexpected outcome or complicated course of recovery. Communication with healthcare providers was considered very important in helping with the recovery process. Conclusion: This research helps to inform healthcare professionals about how they might better support families during complicated recovery processes. Areas of action may include clear communication, setting expectations, and psychosocial support.